RANCANG BANGUN SISTEM INFORMASI KEARSIPAN PADA BAGIAN KEARSIPAN DAN DOKUMENTASI MAHKAMAH AGUNG RI - Ade Suryanto; Rizqy Pratama Putra (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2020)
The Indonesian Supreme Court Archives and Documentation Sub-Section requires an information system that supports and provides satisfactory services for archivists, because the current system is still operated conventionally and has not been computerized. The Supreme Court of the Republic of Indonesia as a judicial institution that applies a modern judicial body, currently records management is still using the manual method, namely by using paper. This can cause several problems including corrupted or lost archive data and spending a lot of time in the process of collecting new records. The best solution is to design a web-based archiving information system using the waterfall method, using several web-based application processing software. Hopefully this is the Supreme Court Archives and Documentation Sub Division of the Republic of Indonesia Supreme Court that is easier to collect data on archives and prevent lost or damaged data. Archive staff also benefit from this system because it will reduce the time to find the required records.